Le triomphe de l’histoire et la ré-invention de la mémoire dans la fiction romanesque de Jean Divassa Nyama - Noël-Bertrand Boundzanga (Les Cahiers de Framespa)
Gabon’s history has been an institutional matter and, from this point of view, it did not report on historical facts that may explain the socio-political phenomena of today. Divassa Nyama’s novel, L’amère saveur de la liberté, discusses the history of colonial resistances, particularly on the Gabonese resistant Nyonda Mackita also known under the name Mavurulu. My thesis is that the manipulation of history to the detriment of the forgotten has been a strong engin for the construction of a slothful Gabonese political identity, bogged down in a wait-and see policy where everything is providential. By returning to the colonial history, the historical novel establishes another memory, a living memory capable of giving to the Gabonese people the meaning of their lives. In this respect, he helps history no to fall into oblivion and gives a new content to collective memories.